The Impact of Brand Image, Service Quality, and Reputation Performance Score on The Purchase Decision: The Role of Customer Engagement - Jaya, Lalu Aswadi; Silitonga, Parlagutan; Nugroho, Sigit Dani; Reyes, Victor T. (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Brand image and Service Quality are usually applied as the main variables on the purchase decision. This research aims to include a Reputation Performance Score to influence Purchase Decisions by Customer Engagement as a mediator variable. The analysis of 260 valid respondents was done using PLS-SEM tools Smart-PLS 3.0. The findings indicated that brand image, service quality, and RPS positively and significantly impacted customer engagement. Therefore, customer involvement, brand image, service quality, and RPS have a favourable and considerable indirect effect on purchase decisions. The role of customer engagement as a mediator variable has made a meaningful contribution to the body of knowledge and marketing practitioners in the hotel industry.